Effective hot-air annealing for improving the performance of perovskite solar cells. (April 2017) - Liu, Yanliang; Shin, Insoo; Hwang, In-Wook; Lee, Jihoon; Kim, Seungmin; Lee, Dal Yong; Lee, Seung-Hoon; Jang, Jae-Won; Jung, Yun Kyung; Jeong, Jung Hyun; Park, Sung Heum; Kim, Kwang Ho
Graphical abstract: Highlights: Novel HAAP method is developed for improving the performance of perovskite solar cell. The HAAP method provides a significant enhancement in crystallinity of perovskite. The device efficiency increased from 9.05 to 15.55% when the HAAP were used. The HAAP device did not exhibit photocurrent hysteresis. Abstract: We report a simple and effective method for improving the performance of CH3 NH3 PbI3−x Clx perovskite solar cells. By employing a moisture pretreatment (MPT) and a novel hot-air annealing process (HAAP) for preparing the perovskite CH3 NH3 PbI3-x Clx film, we could successfully enhance the crystallinity of the CH3 NH3 PbI3-x Clx active layer and improve its photon collection properties. This led to a marked improvement in device performance. Solar cells with the structure indium tin oxide/poly(3, 4-ethylenedioxythiophene) -poly(styrenesulfonate)/CH3 NH3 PbI3-x Clx active layer/[6, 6]-phenyl-C61-butyric acid methyl ester/Ca/Al and fabricated using the MPT process and the HAAP method showed significantly improved performance, including higher power conversion efficiency (PCE) and fill factor values than those of the device fabricated conventionally. The PCE increased from 9.05 to 11.87% when the MPT process was used and from 9.05 to 15.55% when both MPT and HAAP were used. Moreover, the HAAP device did not exhibit photocurrent hysteresis, which is always observed in the case of the conventionally fabricated solar cells owing to the charge traps resulting from the low quality of the perovskite film.